Marine radiocarbon reservoir age simulations for the past 50, 000 years. Issue 16 (31st August 2017) - Butzin, M.; Köhler, P.; Lohmann, G.
Abstract: Radiocarbon ( 14 C) dating calibration for the last glacial period largely relies on cross‐dated marine 14 C records. However, marine reservoirs are isotopically depleted with respect to the atmosphere and therefore have to be corrected by the Marine Radiocarbon Ages of surface waters (MRAs), whose temporal variabilities are largely unknown. Here we present simulations of the spatial and temporal variability in MRAs using a three‐dimensional ocean circulation model covering the past 50, 000 years. Our simulations are compared to reconstructions of past surface ocean Δ 14 C. Running the model with different climatic boundary conditions, we find that low‐latitude to midlatitude MRAs have varied between 400 and 1200 14 C years, with values of about 780 14 C years at the Last Glacial Maximum. Reservoir ages exceeding 2000 14 C years are simulated in the polar oceans. Our simulation results can be used as first‐order approximation of the MRA variability in future radiocarbon calibration efforts. Key Points: We simulate the evolution of marine radiocarbon reservoir ages during the past 50, 000 years Simulated low‐latitude to midlatitude reservoir ages varied between 400 and 1200 14 C years In high latitudes the simulated reservoir ages exceeded 2000 14 C years